Does community-based health insurance reduce disparities in modern health service utilization among households in Ethiopia? A community-based comparative cross-sectional study - Geta, Edosa Tesfaye; Wakjira Bidika, Abebe; Etana, Belachew (Frontiers in Public Health, 2023)
Background: Community based health insurance (CBHI) is an emerging and promising concept to access affordable and effective healthcare by substantially pooling risks to improve health service utilization and equity. While there have been improvements in health care coverage in Ethiopia, disparities in health care remain as a challenge in health care system. Hence, the study aimed to assess the effects CBHI on reduction of disparities in modern health service (MHS) utilization among households. Methods: A community-based comparative cross-sectional study was conducted between February 01 and April 30, 2022 among households in Gida Ayana District, Ethiopia. Double population proportion formula was used to determine 356 sample size and participants were selected using a multistage sampling. Data was entered into Epi-data 4.6 and exported to SPSS 25 for analysis. Results: Among 356 households, 321(90.2%) of them reported at least one member of their family fell in illness in the last six months; 153(47.7%) and 168(52.3%) were among the insured and uninsured respectively. Only 207(64.5, 95% confidence interval (CI)= (59.0-69.7)% of them utilized health services. The level of HSU was 122(79.7, 95% CI=75.5-85.8)% and 85(50.6, 95% CI=42.8-58.4)% among insured and uninsured respectively. Insured households were four times more likely utilized MHS compared to uninsured (Adjusted odds ratio (AOR)=4.27, 95% CI=2.36-7.71). Despite the households being insured, the significant disparities in MHS utilization were observed among households across place of residence (AOR=14.98, 95% CI=5.12-43.82) and education level (AOR=0.20, 95% CI=0.05-0.83). Conclusion: Overall, the CBHI scheme significantly improved the level of HSU and reduced disparities in the utilization across wealth status and family size differences. However, despite households being insured the significant disparities in odds of MHS utilization among households across place of residence and education level were observed. Hence, strengthening the CBHI scheme and focusing on the place of residence and level of education of households are recommended to improve MHS utilization and reduce its disparities.